Progress in laser active detection technology based on the cat’s eye effect - Xinchen Du; Chunrui Wang; Haoran Zhou; Yunfeng Zhang; Jin Guo; Fei Chen (Results in Physics)
Laser active detection technology utilizing the cat’s eye effect is widely applied in rapid reconnaissance, positioning, and target information acquisition. This paper examines the theory of the cat’s eye effect in optical systems and its application in the field of laser active detection. This study assesses the development trend of this technology and the feasibility of implementing long-range target laser active detection. Initially, the working principle of the laser active detection system based on the cat’s eye effect is elucidated. Additionally, this paper compares and analyzes three methods of laser active detection using the cat’s eye effect: geometric optics, physical optics, and angular spectrum propagation. Subsequently, the characteristics and processing methods of cat’s eye target echo data are investigated. Finally, the paper summarizes the main challenges of this technology and assesses its development trends based on engineering requirements. The application of the cat’s eye effect in laser active reconnaissance involves linking the cat’s eye optical system with the target’s optical structure and motion state, optimizing data extraction and recognition algorithms to acquire multidimensional feature information, and enabling real-time detection of high-speed moving targets.